Effect of long-term use of eurycoma longifolia jack on the pancreas in rats: histological assessment - Alfaqeh, Hamoud Hussein Mohammed; Ahmed, Qamar Uddin (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2013)
In recent years, the use of Eurycoma longifolia Jack (ELJ) (Tongkat Ali) has spread dramatically in Southeast Asia especially Malaysia where it is widely used as aphrodisiac and anti-malarial agents. Interestingly, its consumption has become popular in daily life as beverage to enhance energy and stamina especially among males. However, its effect on the safety of vital organs of the body is not studied properly. Hence, the main objective of this study was to determine whether or not long-term use of ELJ has side effects on pancreas in rats. Three different concentrations of aqueous extract of ELJ were prepared and dissolved in distilled water, a total of thirty two Sprague-Dawley male rats were used and randomly divided into three test groups and control. The three test groups were given different doses (low dose 250 mg/kg bw, medium dose 500 mg /kg bw and high dose 1000 mg/kg bw) of aqueous extract of ELJ, respectively. Control group was given distilled water alone. Doses were given orally, daily for about 5 weeks. After 5 weeks, animals were sacrificed; whole pancreas tissues were obtained, fixed in 10 percent formaldehyde solution overnight for histological examination. Histological observations showed no signs of hemorrhage, fatty changes and normal pancreatic tissues in the three test groups when compared to normal. As a conclusion, the daily consumption of ELJ as beverage has no side effect on pancreatic tissue when taken in small quantity for long duration.